WIRELESS SURVEILLANCE CAMERA WITH AMC (AUTOMATIC MOTION CAPTURES) SYSTEM - Ageng Setiani Rafika; Asep Saefullah; Andri Ahmad Gozali (CCIT Journal, 2016)
Nowadays, utilizing surviellence cameras was very popular because is user friendly and it has many usefull as a monitoring and as a part of security system at home, institution, office, etc. The existing surviellence camera using computer as a control system and as a media storage so it’s need a energy and high cost for implementation. Surveillance cameras are designed using the Raspberry Pi B, PIR sensor, webcam Logitech C 170, SD Card, Twitter, Raspbian operating system, and python programming. Automatic input data is performed by PIR sensor that will be detected human around of range area frequently. Output 3.3 - 5 volt (High) will be generated when sensor detected the human around of range area. Otherwise 0 volts output ( Low) will be generated when sensor not detected the human around of range area frequently. Then, The input will be processing by Raspberry Pi using python programming that has made to a command to capture or not.implemetation outcome is a surveillance camera that will capture image in (.jpg) format when the input system detected human around of range frequently. Capture result will save to SD Card that have integrated system. Then the sistem will provide immediately report the situation in a real-time notification through a twitter application device.